A study on median nerve conduction velocity in different age groups - Senthilkumari, K. R.; Umamaheswari, K.; Bhaskaran, Mythili (International Journal of Research in Medical Sciences, 2017)
Background: Nerve Conduction Velocity (NCS) is a test to measure the speed and electrical activity in a nerve. Physiological factors like age, temperature, height, gender affect the nerve conduction velocity. There is paucity on the data regarding the age group at which these changes become significant. Therefore, the aim of the study was to determine the specific age group at which changes in nerve conduction velocity occurs. Methods: 103 individuals in the age group of 15-65 years participated in the study. They were grouped into, Group I in the age group of 15-30 (n=40) years, Group II 31-45 years (n=31), Group III 46-60 years (n=32). Median motor and sensory conduction velocity were determined. Results: There was a significant correlation between age and median motor (p=0) and sensory (p=0) conduction velocities. There was a significant decreasing trend observed in Group III. Conclusions: Age has definite correlation with the NCS in median motor and sensory nerves. It is essential to have reference values with relation to age.